Q. 19

# Solve: (x + y) (dx – dy) = dx + dy. [Hint: Substitute x + y = z after separating dx and dy].

given: (x+y) (dx – dy) =dx+dy

To find: solution of given differential equation

Re-writing the given equation as

Assume x+y=z

Differentiating both sides wrt to x

Substituting this value in the given equation

Now integrating both sides

Formula:

Substituting z=x+y

x-y-ln(x + y)-c=0

ln(x + y) + ln c = x – y

ln c(x + y) = x – y

c (x + y) = ex-y

x + y = 1/c (ex-y)

x + y = d ex-y

where d = 1/c

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Interactive Quiz on DIfferential Calculus50 mins
Interactive Quiz on Differential Calculus | Check Yourself56 mins
Functional Equations - JEE with ease48 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses